1985
DOI: 10.1002/1097-0142(19850615)55:12<2889::aid-cncr2820551232>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Childhood malignancies of the eye and orbit in Northern Nigeria

Abstract: One hundred four histologically proven malignant tumors of the eye and orbit in children seen in Guinness Eye Clinic, Kaduna, Nigeria between 1975 and 1982 are presented. Retinoblastoma and Burkitt's lymphoma account for the majority of the tumors. The data are compared with those from Ibadan, Nigeria. Burkitt's lymphoma occurs less frequently in Kaduna, whereas the incidence of retinoblastoma is almost the same. Chloroma, which was not seen in Ibadan, accounted for 2.9% of the current series. Factors that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The incidence varies around the world with approximately 1 of in 15,000 live births affected in the United States of America compared to 1 in 18,000 live births in Asia (Abiose et al, 1985;Klauss et al, 1990;Ajaiyeoba et al, 1992;Owoeye et al, 2006). This study showed that the majority of patients (64%) presented with unilateral retinoblastoma and the remaining (36%) are bilateral.…”
Section: Discussionmentioning
confidence: 63%
“…The incidence varies around the world with approximately 1 of in 15,000 live births affected in the United States of America compared to 1 in 18,000 live births in Asia (Abiose et al, 1985;Klauss et al, 1990;Ajaiyeoba et al, 1992;Owoeye et al, 2006). This study showed that the majority of patients (64%) presented with unilateral retinoblastoma and the remaining (36%) are bilateral.…”
Section: Discussionmentioning
confidence: 63%
“…This is similar to the results of earlier reports. 2,5,6,9 Several challenges were observed to be present in our setting when compared with the more developed economies of the world. Late presentation was still common with a mean duration of disease before presentation in hospital of 6 months when advanced disease was already present in the majority of the patients reviewed.…”
Section: Discussionmentioning
confidence: 94%
“…[5] It is claimed that retinoblastoma has a prenatal origin as occurrence is soon after birth [6] and there is a report of prenatal diagnosis of retinoblastoma [7] About half of our patients presented at the age of 3 years compared to 89% that presented before the age of 3 years in other parts of the world. [8] Retinoblastoma is also said to be commoner in African than Caucasian children, [9] and is characterized by late presentation in Africa.…”
Section: Discussionmentioning
confidence: 98%